An analysis of the development of Russian "nationalist" music in the 18th-early 20th century - Shi, Weiting (Transactions on Social Science, Education and Humanities Research, 2024)
In the study of Russian music in the 21st century, there are voices against "nationalism”. To make an objective and comprehensive evaluation, this paper reviews Russian music's development from the 18th century to the beginning of the 20th century according to the concreteness and variability of "musical nationalism". The paper believes that Russian "musical nationalism" sprouted in the 18th century, developed and matured in the 19th century, and then began to transform and change in the 1890s, showing different characteristics in three stages, with outstanding historical contributions.